1946
DOI: 10.1002/jcp.1030280102
|View full text |Cite
|
Sign up to set email alerts
|

The action of quinine on dehydrogenases of E. coli

Abstract: Pi inceton Unia ersity, New J t i .(I , I / SIX FIGURRSThe eiYects of quiniiic and related alkaloids have been studied on a number of extracted enzymes as well as on more complex biological processes such as respiration, growth, viability of cells and othey phenomena of interest in the mode of action of these drugs (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1946
1946
1992
1992

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Johnson et al [1,2] were the first to use microorganisms in studies on the kinetics of bacterial luminescence under high pressure. They also reported the effects of quinine on the growth and disinfection of Escherichia coli at increased pressures [3]. More recently, there has been renewed interest in the effects of high pressure on microorganisms, especially in relation to food processing and marine microbes.…”
Section: Introductionmentioning
confidence: 99%
“…Johnson et al [1,2] were the first to use microorganisms in studies on the kinetics of bacterial luminescence under high pressure. They also reported the effects of quinine on the growth and disinfection of Escherichia coli at increased pressures [3]. More recently, there has been renewed interest in the effects of high pressure on microorganisms, especially in relation to food processing and marine microbes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies it has been shown that reactions involving proteins, both in living cells and in extracts, are often accompanied by large volume changes of activation or reaction, respectively: e.g., bacterial luminescence (4,11,12,13,16,17,19), sol-gel changes in myosin and other systems (21), bacterial growth and disinfection (18), denaturation of purified serum globulin and egg albumen (14,15), inactivation of specific antitoxin (20), and specific precipitation (5). Under conditions favoring protein denaturation, such as increased temperature, alkaline pH, or the presence of certain drugs such as alcohol, the application of hydrostatic pressures up to some 700 atm.…”
mentioning
confidence: 99%